Modular-based modeling of electric vehicle thermal management system: Modular system implementation in Simulink - Heydarnezhad Karimi, Babak; Wirsén, Noah (My University, 2021)
There are many advantages coupled to the transition from conventional internal combustion engines (ICEs) to battery electric vehicles (BEVs). From an environmental standpoint, BEVs are generally associated with less emissions, resulting in cleaner air in cities and lower contribution to climate change. To replace the ICEs, the energy efficiency of a BEV needs to be maximized. If that regard, an optimized thermal management system plays a vital role. Thermal management system ensures not only higher energy efficiency but also longer range, increased lifespan of the internal components, reduced running cost, etc. This project aims to develop a novel modeling methodology for the BEV thermal management from the system perspective. The goal was to perform simulations at low computational costs while capturing the relevant physics of the system with good accuracy. The work comprised several steps: become familiar with the existing thermal management system, collecting data from simulations, experiment and supplier, processing data in the form of regression, model the data in a system format for different boundary conditions and finally validate the system for different driving scenarios and ambient conditions. In this methodology, three physical properties are considered: mass flow rate and pressure to validate the system from a fluid perspective; and temperature to consider the thermal aspect. A component-based modeling approach was employed making it possible to capture the behaviour of the individual components and their interactions. The approach is very robust since once the components properties are mapped, the model can be used in multiple thermal management layouts. The developed model was successfully validated from the flow perspective with the pump component having the biggest impact in the model performance. The pumps were modeled with high accuracy within 5 % error margin, and the system produced accurate results for mass flow rate, temperature and pressure. The thermal validation was performed for different driving scenarios such as highway, city driving and WLTC. The system followed similar trends in the mass flow rate, temperature difference and pressure drop over each component compared to GT-SUITE simulations. The model has great potential to serve as a virtual test bench for different design concepts. The usage of the model will substantially reduce the simulation time and efficient optimization procedures, during both physical and virtual testing.
Keywords: BEV; Simulink; GT-SUITE; Thermal management system; Driving cycle; Cooling system; Modular approach